2002
DOI: 10.1007/s00234-002-0856-1
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous vertebroplasty: long-term clinical and radiological outcome

Abstract: We assessed radiographic and functional outcome in 13 patients with a minimum of 5 years follow-up from a prospectively monitored series of 17 patients who underwent percutaneous vertebroplasty (PPV). A visual analogue scale (VAS) and the short McGill questionnaire (MPQ) were used to assess average symptoms. The VAS showed significant improvement after treatment: the initial score was 9.07+/-0.6 (mean+/-SD), falling to 2.07 (1.14) on the third day, 1.07 (1.07) by the third month and 2.15 (2.6) at 5 years. Pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(21 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…In the present study, symptom improvements were shown with the reduced VAS value by 5 marks on a short-term basis. Likewise, satisfactory reductions in clinical symptoms were reported through the long-term studies including 1 year or more of follow-up on a group of 25 patients conducted by Grados et al [7], and 5 years or more of follow-up on a group of 13 patients conducted by Pérez-Higueras et al [8]. We also confirmed the effectiveness of the procedure with reduced and then maintained VAS value by 5 marks or more in 46% of the total cases.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the present study, symptom improvements were shown with the reduced VAS value by 5 marks on a short-term basis. Likewise, satisfactory reductions in clinical symptoms were reported through the long-term studies including 1 year or more of follow-up on a group of 25 patients conducted by Grados et al [7], and 5 years or more of follow-up on a group of 13 patients conducted by Pérez-Higueras et al [8]. We also confirmed the effectiveness of the procedure with reduced and then maintained VAS value by 5 marks or more in 46% of the total cases.…”
Section: Discussionmentioning
confidence: 92%
“…PMMA is a comparatively stable cement and has been widely used. According to the 5-year radiologic results reported by Perez-Higueras et al [8], there were no cases of dislodgment, cracks or vertebral collapse in the 13 cases of injected cement. Tsai et al [14] reported a rare case of anterior dislodgment accompanied with neurologic symptoms in the bone cement injected after surgery that required additional surgery.…”
Section: Discussionmentioning
confidence: 95%
“…Short-term pain relief has been demonstrated in osteoporotic and tumor fractures treated with vertebroplaty and kyphoplasty [47,48] . Long-term outcomes have not been so well established, although some reports state that the beneficial effects of vertebroplasty remain after a followup period of several years [49,50] .…”
Section: Clinical Success Of Vertebroplasty and Kyphoplastymentioning
confidence: 98%
“…23,24 It is also a safe procedure with rare complications. 25 According to Hierholzer et al, 26 most patients who undergo osteoplasty experience immediate and dramatic pain relief following the procedure.…”
Section: Discussionmentioning
confidence: 99%